An economic comparison of reduced tillage and no-till crop production in western Kansas with and without opportunity cropping - Smith, Ray P. (Kansas State University, 2007)
This thesis analyses the economics of reduced tillage farming compared to no-till on a western Kansas farm using elevated crop residue levels and higher intensity opportunity cropping strategies to overcome obstacles. Farming expenses are from the author’s farm. Crop yields and rainfall data come from the Tribune Unit of the KSU-Southwest Research-Extension Center. Price and crop insurance data are from USDA sources on the Internet. Crop enterprise budgets are used to determine per acre expenses, net revenue, and the risks of high cropping intensity no-till (NT), and reduced tillage (RT), eco-fallow and with and without opportunity cropping. Grain sorghum was added to the NT rotation, the RT opportunity cropping and the NT opportunity cropping to potentially increase revenues and compete against perennial grasses. However, grain sorghum revenues for various reasons did not cover average variable costs. Results indicate that NT opportunity cropping can be as or more profitable than RT eco-fallow using corn, however risks and expenses are greater. Over the 10-year study, the NT opportunity cropping averaged $3.97 more net revenue than the RT rotation. The NT rotation averaged $5.40 less net revenue than the RT rotation. The RT opportunity cropping averaged $3.83 less net revenue than the RT rotation. The NT opportunity cropping produced the highest net revenue, followed by the RT rotation. The RT opportunity produced the third highest net revenue and the NT rotation produce the lowest net revenue. The RT rotation showed relatively little risk in the ability to recover variable expenses. These results only apply to this farm and should be extrapolated to other regions only after study and analysis. This case study is not necessary applicable to other farms. However, the ideas and analytical techniques may be used to address similar issues on other farms. This analysis reveals that higher intensity no-till cropping can increase net revenues as long as intensity is decreased when soil moisture at planting is not adequate. This allows farmers to benefit from increases in soil organic matter and decreases in soil erosion from no-till farming.
Keywords: Economic; No-till; Opportunity Cropping; Rotation; Semiarid; Western Kansas; Economics, Agricultural (0503)